Waiting for Godot? : The Case for Climate Change Adaptation and Mitigation in Small Island States - Cevik, Serhan (IMF Working Papers; Working Paper ;, 2022)
Global warming is the most significant threat to ecosystems and people's health and living standards, especially in small island states in the Caribbean and elsewhere. This paper contributes to the debate by analyzing different options to scale up climate change mitigation and adaptation. In particular, the empirical analysis indicates that increasing energy efficiency and reducing the use of fossil fuel in electricity generation could lead to a significant reduction in carbon emissions, while investing in physical and financial resilience would yield long-run benefits. From a risk-reward perspective, the advantages of reducing the risks associated with climate change and the health benefits from higher environmental quality clearly outweigh the potential cost of climate change mitigation and adaptation in the short run. The additional revenue generated by environmental taxes could be used to compensate the most vulnerable households, building a multilayered safety net, and strengthening structural resilience.